THE EFFECT OF HEXAGON MODEL FRAUD ON FINANCIAL REPORT FRAUD (EMPIRICAL STUDY ON INDUSTRIAL SECTOR COMPANIES LISTED ON THE IDX IN 2020-2022) - Hani Rahmawati; Reka Ayu Rahmawati; Ahmad Raihansyah (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Fraud cases are increasing from year to year and the most detrimental is financial statement fraud and causes losses for companies and users of financial statements. This study aims to analyze the fraud hexagon factors in detecting financial statement fraud in industrial sector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. The sampling method used in this study is purposive sampling. The samples that met the research criteria were 33 industrial companies. The data analysis method uses the logistic regression method with the help of the EViews application to test the data. The results of the study indicate that financial targets, external pressure, ineffective supervision, change of auditors, change of directors, collusion and frequent appearance of CEO photos have no effect on detecting financial statement fraud.